Factors Influencing The Decision To Buy Cigarettes In South Tangerang - Zardiana Zardiana; Carunia Mulya Firdausy (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of television advertising, price, and product quality on the purchase decisions of SM cigarette consumers in South Tangerang City. The three variables were selected based on observations of the dynamics of the cigarette market in urban areas which have a high level of spending on tobacco products, as well as diverse consumer characteristics in terms of age, occupation, and income. This study uses a quantitative approach with a survey method of 200 respondents who are active consumers of SM cigarettes. The sampling technique used purposive sampling, with respondent criteria including domiciled in South Tangerang, at least 18 years old, and having purchased cigarettes in the last three months. Data analysis was carried out using the Structural Equation Modeling model based on Partial Least Squares (PLS-SEM). The results of the analysis show that television advertising has a positive and significant influence on purchasing decisions. This indicates that clear television advertisements, attractive messages, and giving trust play a role in encouraging consumers to choose cigarette brands. The price of cigarettes has also been proven to have a significant influence on the decision to buy cigarettes, especially if the price of the cigarettes is worth the value of the cigarettes offered. Product quality is the third significant factor that influences consumer decisions, particularly in terms of packaging, clarity of information, and taste excellence.